Current and emerging pharmacotherapy for the treatment of infections following open-heart surgery. (13th April 2019) - Giacobbe, Daniele Roberto; Corcione, Silvia; Salsano, Antonio; Del Puente, Filippo; Mornese Pinna, Simone; De Rosa, Francesco Giuseppe; Mikulska, Malgorzata; Santini, Francesco; Viscoli, Claudio
ABSTRACT: Introduction : Patients undergoing open-heart surgery may suffer from postoperative complications, including severe infections. Antimicrobials to treat infectious complications in this population should be selected thoughtfully, taking into account three different and fundamental issues: ( i ) the site of infection; ( ii ) the suspected or proven causative agent and its susceptibility pattern; and ( iii ) the risk of suboptimal pharmacokinetic characteristics and potential toxicity of the chosen drug/s. Areas covered : The present narrative review summarizes the current and future antimicrobial options for the treatment of infections developing after open-heart surgery. Expert opinion : The pharmacological treatment of infections developing in cardiac surgery patients poses peculiar challenges, including the need for an active empirical therapy for severe events such as bloodstream infections, deep sternal wound infections, or early-onset postoperative prosthetic endocarditis. In addition, the risk for multidrug-resistant pathogens should also be taken into account in endemic areas. A multidisciplinary evaluation on a patient-by-patient basis, deeply involving infectious diseases specialists and cardiothoracic surgeons, remains essential for appropriately balancing both short-term and long-term risks and benefits of any possible surgical reintervention in combination with adequate pharmacotherapy.